2007
DOI: 10.1007/s11255-007-9226-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to erythropoietin hypo-responsiveness in patients on chronic peritoneal dialysis

Abstract: Background The present study was aimed at investigating the factors related to hypo-responsiveness to erythropoietin in patients on chronic peritoneal dialysis (PD). Methods We studied 44 patients with end-stage renal disease who had been on PD for more than 6 months and on erythropoietin (EPO) !6,000 U/ week for more than 3 months. We expressed EPO resistance index (ERI) as weekly EPO dose per hematocrit (Hct) per body weight. The dose of EPO was titrated to maintain a target Hct level between 33% and 36%. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
3
16
1
Order By: Relevance
“…Nevertheless, it has been suggested that increased production of these cytokines may account for recombinant human erythropoietin (rhEpo) hypo-responsiveness. Therefore, reduction of infl ammatory cytokines can improve haematological status in advanced renal failure patients (Kim et al, 2001;Wei et al, 2007). In summary, these studies support the concept that silymarin antagonizes the action of pro-infl ammatory cytokines in treating infl ammatory anaemia in peritoneal dialysis patients.…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, it has been suggested that increased production of these cytokines may account for recombinant human erythropoietin (rhEpo) hypo-responsiveness. Therefore, reduction of infl ammatory cytokines can improve haematological status in advanced renal failure patients (Kim et al, 2001;Wei et al, 2007). In summary, these studies support the concept that silymarin antagonizes the action of pro-infl ammatory cytokines in treating infl ammatory anaemia in peritoneal dialysis patients.…”
Section: Discussionsupporting
confidence: 57%
“…When we compared the 3 groups regarding the ESA/Hb index, we observed that the main differences between groups, were related to inflammatory and nutritional parameters. These findings have been well described in patients undergoing maintenance renal replacement therapy [14,[34][35][36]. Inflammation can interact with the hematopoietic system at different levels, inhibiting erythropoietin secretion and erythroid progenitor cells maturation, increasing red blood cells destruction and decreasing iron delivery from reticuloendothelial to hematopoietic cells [12,37].…”
Section: Discussionmentioning
confidence: 84%
“…Increased proinflammatory cytokines inhibit hepatic albumin and pre-albumin syntheses and also lead to erythropoiesis impairment. [19][20][21][22] Previous data have suggested close relationships between low serum albumin levels and CRP concentrations, 23 CVD development, 24 and mortality in PD and HD patients. 25,26 Low HDL-cholesterol level is related to atherogenesis, and according to our study, increased N/L ratio was accompanied by decreased HDLcholesterol levels.…”
Section: Discussionmentioning
confidence: 99%